2019
DOI: 10.1002/jimd.12015
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac disease in mucopolysaccharidosis type III

Abstract: Mucopolysaccharidosis type III (MPS III; Sanfilippo disease) is primarily characterized by neurocognitive decline with limited somatic disease. Only few reports addressed cardiac disease (CD) in MPS III. We investigated the prevalence of CD in a relatively large cohort of patients. In this cross‐sectional study, extensive echocardiographic studies were performed in 30 MPS III patients (16 patients <18 years), all without clinical symptoms of CD. Results were compared to data from matched controls. The mean glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 41 publications
3
20
0
1
Order By: Relevance
“…MPS was related to myocardial deformation and more impaired diastolic function and a decline in the global LV systolic mechanics, despite globally preserved LV ejection and shortening fractions. These results were consistent with those of previous studies [21,27,28].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…MPS was related to myocardial deformation and more impaired diastolic function and a decline in the global LV systolic mechanics, despite globally preserved LV ejection and shortening fractions. These results were consistent with those of previous studies [21,27,28].…”
Section: Discussionsupporting
confidence: 94%
“…Consequently, using myocardial deformation imaging in clinical practice may be of value in the early diagnosis of myocardial dysfunction. However, STE has not yet been broadly used to evaluate myocardial mechanics in patients with MPS [21,27,28]. In this study, we aimed to determine the cardiac structure and function of Taiwanese patients with various MPS types using 2D STE and conventional echocardiography.…”
Section: Introductionmentioning
confidence: 99%
“…Although LV systolic function according to ejection fraction and shortening fraction values was normal in all of our patients, however, ejection fraction and shortening fraction values are parameters that show abnormalities when there is substantial LV dysfunction. Speckle-tracking echocardiography is a marker for early, subclinical LV dysfunction which was recently reported in patients with MPS III by Nijmeijer et al [23]. In our study, a reversed E/A ratio (< 1) was identified in one patient (4%).…”
Section: Discussionsupporting
confidence: 70%
“…Cardiac involvement in MPS III has been reported to be less common and milder compared with the other types of MPS [2, 10, 2023, 37]. Nijmeijer et al [23] reported mitral valve abnormalities and aortic valve abnormalities in 13/30 (43%) and 10/30 (33%) patients with MPS III, respectively. Consistently, echocardiographic examinations in our cohort also revealed that 35 and 27% of the patients had mitral valve abnormalities or aortic valve abnormalities, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation